LEGAL PROTECTION OF FIDUCIARY HOLDERS BASED ON CONSTITUTIONAL COURT RULING NUMBER. 18/PUU-XVII/2019 - Putra, Januanwar Reza Yudhitya; Subekti, Subekti; Prawesthi, Wahyu; Widodo, Ernu (SYNTIFIC, 2024)
Background. Legal certainty is significantly enhanced by fiduciary guarantees as a result, the research aimed (a) to develop knowledge of business law, especially banking law, especially regarding credit with Fiduciary Guarantees, (b) to contribute parties related to activities that often use contracts with fiduciary guarantees such as banking and society Research Method. The type of research used is a normative juridical approach to answer existing research problems, using legal principles, statutory regulatory materials, and theoretical frameworks. The analysis of library materials and secondary data to gain a comprehensive understanding of the subject matter. Findings. The results showed (a) the procedure of carrying out an object of fiduciary guarantee requires submitting an execution request to the District Court. This court functions as an intermediary, granting permission for execution to aggrieved creditors. If the agreement itself has the power of execution, then the fiduciary guarantee can be executed immediately (b) The recent Constitutional Court decision Number 18/PUU-XVII/2019, states that every person has the right to recognition, guarantees, protection, fair legal certainty and equal treatment before the law. This law functions to enforce human rights contained in the 1945 Constitution, guaranteeing justice and protection all society. Conclusion. Constitutional Court decision No. 18/PUU-XVII/2019 raises various problems that are not in line with the provisions of Law No. 42 of 1999 concerning Fiduciary Guarantee. Following this decision, banks as creditors no longer carry out executions unilaterally. If the debtor is in default and has created injustice and ambiguity for creditors by eliminating the authority.